A Study on the Effects of Morphological Changes Due to the Construction of Multiple Coastal Structures - Kyu-Tae Shim; Kyu-Han Kim (Journal of Marine Science and Engineering)
The study area was Anin Beach, where a 1.48-km-long breakwater, consisting of a non-porous caisson, was constructed over 16 months. During this process, significant erosion occurred over a wide area behind the coast, with a maximum reduction in the beach width of 36 m observed in the central part of the coastline. As a countermeasure to prevent erosion, a submerged breakwater was installed that consisted of concrete blocks and had a length of 600 m. Following the implementation of this submerged breakwater, the beach behind it increased in width by 64 m, in proportion to the installation length, while erosion phenomena, such as the loss of coastal roads, were observed at both ends of the structure. In this study, the topographical changes caused by waves and currents were analyzed to identify their causes and establish countermeasures. Additionally, the planned measures, established before structure installation, were closely examined against the actual occurrences observed onsite through a coastline survey.